2014
DOI: 10.1071/an14335
|View full text |Cite
|
Sign up to set email alerts
|

Rice straw, cassava by-products and tree legumes provide enough energy and nitrogen for liveweight maintenance of Brahman (Bos indicus) cows in Indonesia

Abstract: The aim of this experiment was to test the effectiveness of two diets in increasing liveweight (LW) and body condition score (BCS) of Brahman cows in Indonesia. Diets were based on rice straw, with additional energy and nitrogen (N) provided in the form of onggok (a cassava by-product) plus urea or a tree legume. Thirty mature, non-pregnant, non-lactating Brahman crossbred cows (288 kg LW, BCS 2/5) were allocated to one of two treatment groups. Cows were kept in individual pens for 21 weeks and offered one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…No differences in total feed intake were found in Ongole cross (Bos indicus) cows (318 ± 12 kg LW) fed rice straw ad libitum with supplemented four levels of legumes (Gliricidia sepium and Leucaena leucocephala) (0, 11, 21, and 42 g DM/kgW 0.75 day) for 20 weeks (Syahniar et al, 2012). Similarly, Antari et al (2014) reported that there was no significant differences in total DM and ME intake or rice straw intake between mature Brahman (Bos indicus) cows fed on two different diets of fed rice straw and onggok plus urea or gliricidia in Indonesia. Onggok is a fibrous cassava by-products left after starch has been extracted from the tuber, whereas gliricidia is a leguminous tree belonging to the Fabaceae family.…”
Section: Discussionmentioning
confidence: 96%
“…No differences in total feed intake were found in Ongole cross (Bos indicus) cows (318 ± 12 kg LW) fed rice straw ad libitum with supplemented four levels of legumes (Gliricidia sepium and Leucaena leucocephala) (0, 11, 21, and 42 g DM/kgW 0.75 day) for 20 weeks (Syahniar et al, 2012). Similarly, Antari et al (2014) reported that there was no significant differences in total DM and ME intake or rice straw intake between mature Brahman (Bos indicus) cows fed on two different diets of fed rice straw and onggok plus urea or gliricidia in Indonesia. Onggok is a fibrous cassava by-products left after starch has been extracted from the tuber, whereas gliricidia is a leguminous tree belonging to the Fabaceae family.…”
Section: Discussionmentioning
confidence: 96%
“…It has been confirmed that the adequacy of cow nutrition has an impact on reproductive performance (Antari et al, 2014;Mayberry et al, 2014). Inadequate nutritional intake for cattle makes cattle body reserves run out and body condition decreases (Diskin andKenny, 2016, 2014).…”
Section: Reproductive Performance Of Beef Cattle In Different Productmentioning
confidence: 99%
“…Beef cattle are usually operated by farmers and aim for cow-calf operation or fattening (Agus and Widi, 2018;Ekowati et al, 2018). Some studies have informed that the productivity (reproductive aspect) of beef cattle kept by smallholder farmers is still relatively low, especially in the reproductive aspect (Antari et al, 2014;Dahlanuddin et al, 2016;Agus and Widi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Improved BCS and nutrition may also have improved corpus luteum viability and embryo survival. For smallholders, high quality green feeds (such as gliricidia, sesbania, leucaena) are a good source of protein (Antari et al 2014a) and highly digestible energy to increase reproduction performance.…”
Section: Feeding Managementmentioning
confidence: 99%
“…Brahman cattle have a large mature size and a faster growth rate (Tatman et al 2004) than local Indonesian cattle (e. g. Bali (Bos javanicus) and Ongole (Bos indicus) breeds), when they are managed well and kept in good condition. However, Brahman cows also have higher maintenance energy requirements compared to local cattle (Antari et al 2014a;Antari et al 2014b), and many smallholder farmers have reported problems with low growth rates and long inter-calving intervals (Ciccioli et al 2003). This means that farmers invest considerable amounts of time, labor and money before they have a calf ready for sale.…”
Section: Introductionmentioning
confidence: 99%